Exploring The Muslim Millenials Perspective On Financial Well-Being - Ningtyas, Mega Noerman; Cahyaningtyas, Fadilla (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2024)
This research explores the view of financial well-being from the unique perspective of the Muslim millennial generation, considering the economic transitions and technological advancements shaping their financial behaviors to become more consumptive. Through qualitative interviews, the research delves into the subjective perceptions, behavioral patterns, and socio-economic factors that influence the financial well-being of moslem millennials. Furthermore, this research also identifies the key determinants of their financial well-being, including financial literacy, financial behavior, and financial stress. Our findings contribute to a deeper understanding of the complexities surrounding financial well-being in the millennial cohort, providing valuable insights for policymakers, financial institutions, and individuals aimed at enhancing financial health and resilience among Muslim millennials.